Kanoničke relacije između bazičnih i specifičnih motoričkih sposobnosti organizma - Dodig, Miroslav (Promet - Traffic&Transportation, 2012)
The paper deals with the system of basic and specific body motor capacities with reference to rescue at sea by using the canon relation. The survey has been completed on the sample by using a set of variables and a series of tests of basic and specific body motor capacities and elements of rescue. The patter of variable intercorrelation has been analyzed. A relatively high degree of correlation of motor capacities and elements of rescue comes as a result of impacts of repetitive and explosive strength, speed of coordination, and ability of completing motor capacity related tasks.